“The Potter’s wheel”. Mouldmade Ware in the Ionian-Adriatic basin between main workshops and branches: the case of southern Illyria (Archaeologia Adriatica, 2026)
Hellenistic Mouldmade Ware originated in Athens in the last quarter of the 3rd century BCE, drawing inspiration primarily from metal prototypes. The production quickly spread, with new workshops emerging in Asia Minor and throughout the eastern Aegean region before establishing a presence in the central Mediterranean. The Ionian-Adriatic basin became one of the most significant areas involved in the production of this ceramic class. Among the recognized production districts, the southern Illyrian district stands out, with Durrës as its main centre. Several other sites likely functioned as satellite workshops of Dyrrhachium, as evidenced by the strong similarities in the morphological and decorative repertoire of the pottery produced.
Keywords: Durres; Hellenistic Pottery; Illyria; Mouldemade Ware; Pottery; Zgërdhesh